Un programa de fisiología animal para la enseñanza de pregrado ajustado a los objetivos del plan de estudios en la formación del médico Veterinario Zootecnista. - Álvarez Díaz, Armando (2015)
Teaching Physiology Science change between Universities in dependence of type formation due to institutional purpose for necessity of region or country, The contains, teaching methods and evaluation system need to be open for confrontation with the real professional practice which need the society. Animal Physiology is a part of Biology that explains the development of vital body processes charge of animal live in close relation with the environment. From traditional point of view, Animal Physiology teaching in our degree is based in a system of knowledge for system which explains the functioning of animal body cause of that, its program and books maintain this organization. The objective of Animal Physiology is not the same that Human Physiology because this one explains only the functioning of one specie and the other need to explain the functioning at least of ei¬ght domestic animal species (cows, sheeps, goats, horses, pigs, dogs, cats and chickens) raison for what need to explain its multiples particularity, that means, need to be comparative and applied in function of animal live and production conditions. The present work suggest a program of Animal Physiology which take into account in logical order first Basic Physiology and later Applied Physiology in the way to satisfy the real requirement of future professional.